EXTRAJUDICIAL DISPUTE RESOLUTION: CONSENSUAL MECHANISMS, EFFECTIVENESS, AND PROTECTION OF HEALTH IN RELATION TO DENTISTRY - Cossaros, Beatriz Andreia Melo Silva (Seven Editora, 2026)
The increasing judicialization of conflicts between dentists and patients highlights the limitations of an exclusively adjudicative approach in disputes characterized by high technical, relational, and informational complexity. This article comparatively analyzes the Brazilian and Argentinian systems of extrajudicial conflict resolution in dentistry, emphasizing mediation and the role of extrajudicial advocacy, evaluating their impacts on the effectiveness of health protection and professional civil liability. It starts from the premise that many controversies do not stem from pure technical error, but from communication and informational failures related to expectations of results, understanding of the therapeutic plan, foreseeable risks, costs, and clinical documentation. In this context, the ancillary duties of objective good faith—information, informed consent, medical records, and cooperation—are examined as structural elements capable of reducing uncertainties and favoring proportionate solutions. It concludes that mediation constitutes an appropriate method, without excluding jurisdiction when necessary.